Pengembangan Modul IPA Terpadu Kompetensi Konsep Alat Optik Dengan Pendekatan Multirepresentasi Di SMP Sungai Raya - Yesinta, -; Andy, -; Stepanus, - (Universitas Tanjungpura, 2016)
The purpose of this study to obtain objective information and explanations about the development of the module with multirepresentasi approach in improving the understanding of physics concepts learners of Junior High School of Christiani Immanuel 2 Sungai Raya. The method used in this research is the research and development using a model Borg & Gall. The tool of data collection that is used in the form of guidance interviews; test questionnaire, the content, instructional media expert test, and one by one; as well as tests. Results of the research is a module approach multirepresentasi the concept of optical instrument that has the following sections: a) the opening section consist of (cover, a review of subjects, content, concept maps, and indicators of learning), b) the main part consist of (introduction, learning activities (goal, description of the material presented using representations verbal, of physics and mathematic, summaries, exercises, formative tests, key’s answer, as well as feedback and follow-up), and conclusion), and c) at the last (the final test, glossary and references). This module has a level of effectiveness of the cognitive aspects of learning acquisition of 79% as well as it very attractive, it easy, and it is very beneficial for the students to learn the material optical instrument